PEDAGOGICAL- PSYCHOLOGICAL BASIS OF DEVELOPMENT OF COMMUNICATIVE AND LINGVOCULTURAL COMPETENCE OF FUTURE TRANSLATORS (Scientific journal of the Fergana State University, 2023)
This article describes the opinion that the development of linguistic, cultural and communicative competence of future translators is an important factor in the development of pedagogical and psychological foundations.